Comment évaluer la qualité d’une formation pour l’améliorer ? - Alexia Stumpf; Paul-André Garessus (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In higher education, the tools which aim to evaluate quality, especially those that hand over to students, spread these last years. These tools and the process in which they are part of aim to evaluate the quality of various objects as for example teaching, school curricula, learning etc. If evaluation is thought in a formative way aiming the professional development of the evaluated object (teacher or training stream for example) then it’s legitimate to ask oneself if the tools used for evaluation are really favourable for this development. In this article we are questioning the quality of the training in a University of Teacher Education and are beginning with identifying three levels of elements which are supposed to have effect on the quality of training. Then we are showing an analysis process of evaluative tools aiming to determine to what extent they are asking the students’ perceptions about these influent levels. We are showing this process in its most general features in order to let it be transferable to other contexts of higher education. And then we are showing the way this process has operated in our University of Teacher Education in Switzerland in letting show to what extent it contributes to the understanding of the studied evaluating tool, its evolution, or its impact on the management of a training stream. Finally, we are identifying some limits associated to this process and pointing some possible ways of evolution.